The Students' and the Teachers' Perception of the Washback Effect of the English Progress Test - Jati Suryanto; Maryam Sorohiti; Isdiarto Isdiarto; Bivy Callista Putri Alya; Affra Zahra (Research and Innovation in Social Science Education Journal (RISSEJ), 2023)
Tests can directly impact educational processes in various ways. It means that the test may influence the students and the teachers. This influence is called washback or backwash. Washback or backwash is generally known as the effect of testing on teaching and learning (Djuric, 2008). The local government usually prepares formative and summative tests in the school while the teachers design the progress test. This research investigates the washback effect of the English progress test on the students and teachers in one reputable senior high school in Yogyakarta. This research used a qualitative descriptive method. Interviews and focus group discussions were used as methods of data gathering. The respondents were three English teachers and 16 students of12th-grade at a public senior high school in Yogyakarta. The research focused on how the progress test gave a washback effect to the teachers as the test developers and what the students' perception was of the washback effect of the progress test. It concluded that washback effects for teachers depended on 1) focusing on the objective of teaching, 2) the teaching materials, and 3) the teaching methodology. Meanwhile, the effects on students were 1) influencing the learning strategy, 2) preparation for doing tests, 3) improving the learning motivation, the learning mastery, and the learning-teaching atmosphere.